2020
DOI: 10.18632/aging.103208
|View full text |Cite|
|
Sign up to set email alerts
|

Establishing immune scoring model based on combination of the number, function, and phenotype of lymphocytes

Abstract: The immune system plays a crucial role in maintaining body health, not only by protecting the host against pathogenic agents including bacteria, fungi and virus but also by eliminating aged, mutant or dead cells in the body [1-3]. The abnormal immune function can cause many hazards, such as infectious disease, cancer, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…2C – 2D ). The possible reasons of the stromal and immune score difference between >65 group and age ≤ 65 group could be as follows: Firstly, the correlation between immunity and age is a little controversial, with different results in different studies( Hirokawa et al, 2013 ; Tang et al, 2020 ; Weiss et al, 2016 ). Moreover, the original purpose of TCGA project is to design for molecular study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2C – 2D ). The possible reasons of the stromal and immune score difference between >65 group and age ≤ 65 group could be as follows: Firstly, the correlation between immunity and age is a little controversial, with different results in different studies( Hirokawa et al, 2013 ; Tang et al, 2020 ; Weiss et al, 2016 ). Moreover, the original purpose of TCGA project is to design for molecular study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, high ARL4C expression is an essential prognostic factor in LUAD (Kimura et al, 2020). However, a single gene biomarker is insufficient to produce comprehensive predictive effects and immune prognostic models were proposed for LUADs recently (Luo et al, 2020;Yang et al, 2019;Yue, Ma & Zhou, 2019). Until now, only few biomarkers for LUADs have been developed and there is a need to identify more pathways for new biomarkers including sensitive biomarkers which can provide individual therapeutic strategies for patients.…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of lymphocyte function should be conducted before chemotherapy at each time point. PMA/ionomycin-stimulated lymphocyte function assay was performed as described in our previous studies [ 16 , 17 ]. The procedures were described as follows: 1) 100 µl of whole blood was diluted with 400 µl of IMDM medium; 2) the diluted whole blood was stimulated with Leukocyte Activation Cocktail (Becton Dickinson GolgiPlug) for 4 h; 3) the cells were stained with the following monoclonal antibodies anti-CD45-PerCP (652,803), anti-CD3-TITC (349,201), anti-CD4-APC/H7 (341,115), anti-CD56-PE/Cy7 (652,825), and anti-CD8-PE (340,046), followed by fixation and permeabilized (554,722), and staining with intracellular anti-IFN-γ-APC antibody (554,702).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, several studies have identified the specific characteristics of the immunophenotype in TB patients ( 28 , 29 ). Furthermore, our team has previously introduced a novel method-lymphocyte function assay for evaluating lymphocyte function ( 30 , 31 ). The test could reflect the activation, chemotaxis, and cytotoxicity of lymphocytes through the percentage of IFN-γ released under PMA/ionomycin stimulation ( 32 ).…”
Section: Introductionmentioning
confidence: 99%